Origin of methane-rich natural gas at the West Pacific convergent plate boundary. Issue 1 (December 2017) - Sano, Yuji; Kinoshita, Naoya; Kagoshima, Takanori; Takahata, Naoto; Sakata, Susumu; Toki, Tomohiro; Kawagucci, Shinsuke; Waseda, Amane; Lan, Tefang; Wen, Hsinyi; Chen, Ai-Ti; Lee, Hsiaofen; et al.
Abstract Methane emission from the geosphere is generally characterized by a radiocarbon-free signature and might preserve information on the deep carbon cycle on Earth. Here we report a clear relationship between the origin of methane-rich natural gases and the geodynamic setting of the West Pacific convergent plate boundary. Natural gases in the frontal arc basin (South Kanto gas fields, Northeast Japan) show a typical microbial signature with light carbon isotopes, high CH4 /C2 H6 and CH4 /3 He ratios. In the Akita-Niigata region – which corresponds to the slope stretching from the volcanic-arc to the back-arc –a thermogenic signature characterize the gases, with prevalence of heavy carbon isotopes, low CH4 /C2 H6 and CH4 /3 He ratios. Natural gases from mud volcanoes in South Taiwan at the collision zone show heavy carbon isotopes, middle CH4 /C2 H6 ratios and low CH4 /3 He ratios. On the other hand, those from the Tokara Islands situated on the volcanic front of Southwest Japan show the heaviest carbon isotopes, middle CH4 /C2 H6 ratios and the lowest CH4 /3 He ratios. The observed geochemical signatures of natural gases are clearly explained by a mixing of microbial, thermogenic and abiotic methane. An increasing contribution of abiotic methane towards more tectonically active regions of the plate boundary is suggested.